Tire pressure monitoring system - Abdul Wahab, Muhammad Hafiz Mohamad; Abdul Rahim, Ruzairi; Abdul Shaib, Mohd.Fadzli; Ishak, Mohamad Hafis Izran; Mohamed Ali, Mohamed Sultan; Wahid, Herman; Abas, Khairul Hamimah; Jamaluddin, Juliza; Tee, Kian Sek (Penerbit UTHM, 2022)
Tire pressure plays an important role in the safety and fuel consumption considerations of automobiles. Vehicles moving with low tire pressure will consume more fuel. Leakage of air from tire, if not detected, can cause serious problems during running of vehicle. The proposed TPMS is designed keeping these vital considerations in view. This system can be integrated in the On-Board Diagnostic (OBD) system of automobiles. There are two basic methods to measure tire pressure; direct and indirect [1]. The direct technique is implemented. Numerous patents and designs have been introduced for tire pressure measurement. These designs recognize the importance of tire pressure measurement. Many companies nowadays are manufacturing TPMS with the pressure measuring unit mounted to the valve stem inside the tire (onto the inner side of rim). This requires modification to the tire. To change the electronic unit or its battery (in case of malfunction or battery replacement) the tire has to be opened. Moreover, the units must have casing strong enough to avoid damage to the units in case of tire burst. Also, different vehicles use different tires and manufacturing a single unit that matches requirement of all tires is a dilemma. A blowout occurs when a flat tire is so severely damaged that immediately loses all air pressure and causes a driver to lose control, which is why it is one of the top causes of car accidents. Most car accident lawyers know that catastrophic and fatal big rig truck accidents are often the result of a major tire blowout. Indeed, all of us have heard about defective tires in the news; but many of the tires, even though defectively designed, might not have blown out if they were properly inflated. This is no excuse for a tire manufacturer. This section will describe some related projects done by other researcher and some news regarding cases of tire burst that cause car accident.